2020
DOI: 10.1186/s12913-020-5016-y
|View full text |Cite
|
Sign up to set email alerts
|

The effect of the look-back period for estimating incidence using administrative data

Abstract: Background: The look-back period is needed to define baseline population for estimating incidence. However, short look-back period is known to overestimate incidence of diseases misclassifying prevalent cases to incident cases. The purpose of this study is to evaluate the impact of the various length of look-back period on the observed incidences of uterine leiomyoma, endometriosis and adenomyosis, and to estimate true incidences considering the misclassification errors in the longitudinal administrative data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 33 publications
(38 reference statements)
1
13
0
Order By: Relevance
“…Studies of lookback periods have been conducted in the context of incidence estimation/phenotype development, effect estimation, with a limited number of studies in the context of prediction [ 2 7 ]. Incidence estimation and effect estimation studies all advise that longer lookback reduces data noise for the diseases and data sources evaluated [ 2 4 ]. The findings from the relatively few prediction studies stated that for the outcomes evaluated that lookback period did not materially impact the model discrimination but did improve identification of the disease history [ 5 7 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies of lookback periods have been conducted in the context of incidence estimation/phenotype development, effect estimation, with a limited number of studies in the context of prediction [ 2 7 ]. Incidence estimation and effect estimation studies all advise that longer lookback reduces data noise for the diseases and data sources evaluated [ 2 4 ]. The findings from the relatively few prediction studies stated that for the outcomes evaluated that lookback period did not materially impact the model discrimination but did improve identification of the disease history [ 5 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies using administrative data and investigating variations in the length of lookback period have been conducted in the context of incidence and effect estimation [ 2 4 ]. In a study of cancer cumulative incidence estimation the authors recommended using lookback of 2 or more years and discouraged the use of 1 year lookback but caveated that it is not possible to provide general recommendations as lookback period is dependent on the characteristics of the cancer site and the available data and the underlying research question [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[3]Studies using administrative data and investigating variations in the length of lookback period have been conducted in the context of incidence and effect estimation [4][5][6]. In a study of cancer cumulative incidence estimation the authors recommended using lookback of two or more years and discouraged the use of one year lookback but caveated that it is not possible to provide general recommendations as lookback period is dependent on the characteristics of the cancer site and the available data and the underlying research question [5].…”
Section: Introductionmentioning
confidence: 99%
“…In a study of cancer cumulative incidence estimation the authors recommended using lookback of two or more years and discouraged the use of one year lookback but caveated that it is not possible to provide general recommendations as lookback period is dependent on the characteristics of the cancer site and the available data and the underlying research question [5]. A Korean study using a cohort database and examining lookback and estimating incidence of three gynecological diseases (uterine leiomyoma, endometriosis, and adenomyosis) found that as the lookback increased the proportion of misclassi ed incident cases decreased but advised that the optimal lookback for annual incidence depended on the nature and the stage of the respective diseases [6]. A comparative effect study using the Medicare bene ciary database and evaluating the effect of statin initiation on incidence of cancer recommended that a three year lookback was best but if infeasible that all available lookback is preferable to short xed lookbacks [4].…”
Section: Introductionmentioning
confidence: 99%